The monetary model of exchange rate: evidence from The Philippines - Chin, Lee; Azali, Mohamed; Yusop, Zulkornain; Yusoff, Mohammed (Routledge Taylor & Francis, 2007)
This note examines the empirical validity of the monetary model of exchange rate determination for The Philippines via cointegration and vector error-correction model. It is found that the monetary model is a valid framework for the long-run exchange rate between Philippines peso-US Dollar exchange rate. However, the typical linear restrictions of flexible-price monetary model and proportionality between the exchange rate and relative money are rejected.